Fibrin Clot Lysis by Thrombolytic Agents Is Impaired in Newborns due to a Low Plasminogen Concentration - Andrew, M; Brooker, L; Leaker, M; Paes, B; Weitz, J (Thrombosis and Haemostasis, 1992)
Although thrombolytic drugs have been extensively used in adults, there is sparse information on their effectiveness in newborns whose fibrinolytic system differs significantly from adults. The purpose of this study was to determine if low plasma levels of plasminogen in cord plasma limited the therapeutic effectiveness of thrombolytic agents. Urokinase (UK), streptokinase (SK) and tissue plasminogen activator (TPA) were compared for their ability to lyse washed 125I-labelled adult or cord fibrin clots suspended in cord or adult plasma. 125I-labelled fibrin clots were prepared by recalcifying cord or adult plasma spiked with labelled fibrinogen and then placed into cord or adult plasma which contained either saline or differing amounts of a specific thrombolytic agent. After a 60 min incubation, the remaining 125I-fibrin in clots released 125I-fibrin fragments, and concentrations of fibrinogen, α2-antiplasmin, and plasminogen in the bathing plasma were measured and compared to starting values. Cord fibrin clots were more resistant than adult fibrin clots to all thrombolytic drugs tested (p <0.001). On average, the cord system retained 27% more 125I-fibrin in clots, and released 32% less 125I-fibrin fragments into plasma. Fibrinogenolysis was also decreased in cord plasmas compared to adult plasmas. The degree of fibrinolysis and fibrinogenolysis in cord plasma increased to adult values when plasminogen concentrations were increased in the bathing plasma. Thus, cord fibrin clots have an impaired response to thrombolytic agents secondary to low levels of plasminogen. We speculate that the clinical response of newborns to thrombolytic agents is also impaired and will not be enhanced by increasing doses of thrombolytic agents but may be enhanced by increasing the concentration of plasminogen.